2017
DOI: 10.1007/s00795-016-0151-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced podocyte vesicle transport in the nephrotic rat

Abstract: Albumin endocytosis is enhanced in the podocytes of minimal change nephrotic syndrome. We investigated that the endocytic vesicle transport in the podocyte using three-dimensional observation in a rat model of puromycin aminonucleoside (PAN)-induced nephrotic syndrome. At day 7, Evans Blue-labeled albumin was intravenously injected in PAN rats, and one kidney was fixed for a morphological analysis; the other was used for the isolation of glomeruli through sieving and protein analyses. Evans Blue-labeled albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Recent emerging evidence supports the notion of albumin transport through the podocyte cell body [26, 27, 30, 32, 35]. In 1955, Rinehart proposed that the glomerular filtrate is transported across the glomerular epithelial cytoplasm via small vesicles [36].…”
Section: Podocyte Vesicle Transport By Dyneinmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent emerging evidence supports the notion of albumin transport through the podocyte cell body [26, 27, 30, 32, 35]. In 1955, Rinehart proposed that the glomerular filtrate is transported across the glomerular epithelial cytoplasm via small vesicles [36].…”
Section: Podocyte Vesicle Transport By Dyneinmentioning
confidence: 93%
“…In 1955, Rinehart proposed that the glomerular filtrate is transported across the glomerular epithelial cytoplasm via small vesicles [36]. Large numbers of endocytic vesicles have been detected in the podocytes of MCNS patients by TEM [35, 37, 38]. Furthermore, a numerous holes have been observed at the basal and apical surface of podocytes [27, 39], suggesting endocytosis and exocytosis of transported proteins (Figure 5).…”
Section: Podocyte Vesicle Transport By Dyneinmentioning
confidence: 99%
See 1 more Smart Citation
“…Manuscript to be reviewed injury. There are several pathways of albumin endocytosis, such as Dynamin-dependent podocyte endocytosis, FcRn-mediated albumin transcytosis (Kinugasa et al 2011), clathrinmediated endocytosis (Soda et al 2012), caveolin-mediated endocytosis (Dobrinskikh et al 2014), fluid phase-endocytosis (Palm et al 2015) and dynein-microtubule related vesicle transport (Tojo et al 2017). Dynamin plays a crucial role in maintaining the structure and function of the glomerular filtration barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that overexpression of Myo1e promoted apoptosis of MPC5 cells that were co-cultured with BSA, indicating that overexpression of Myo1e may induce podocyte injury. There are several pathways of albumin endocytosis, such as Dynamin-dependent podocyte endocytosis, FcRn-mediated albumin transcytosis (Kinugasa et al 2011), clathrinmediated endocytosis (Soda et al 2012), caveolin-mediated endocytosis (Dobrinskikh et al 2014), fluid phase-endocytosis (Palm et al 2015) and dynein-microtubule related vesicle transport (Tojo et al 2017). Dynamin plays a crucial role in maintaining the structure and function of the glomerular filtration barrier.…”
Section: Discussionmentioning
confidence: 99%